Study of the processes of shaping the hollow billets from antifriction alloys by the centrifugal and continuous casting methods - Khoroshylov, O.M.; Kurylyak, V.V.; Podolyak, O.S.; Antonenko, N.S. (Успехи физики металлов, 2019)
The focus of this work is a comparative analysis of the mechanisms of shaping of the hollow billets, which affect the yield of the centrifugal and continuous casting of БрО8Н4Ц2 (Cu 8% Sn 4% Ni 2% Zn) - and БрО5Ц5С5 (Cu 5% Sn 5% Zn 5% Pb) - type bronzes. As revealed, the action of centrifugal forces causes the segregation of chemical elements of the alloys, depending on their density. Цілеспрямованістю роботи є порівняльний аналіз механізмів формування порожнистих заготівок, що впливають на вихід придатного відцентрового та безперервного лиття бронзи марок БрО8Н4Ц2 (Cu 8% Sn 4% Ni 2% Zn) і БрО5Ц5С5 (Cu 5% Sn 5% Zn 5% Pb). Целенаправленностью работы является сравнительный анализ механизмов формования полых заготовок, влияющих на выход годного центробежного и непрерывного литья бронзы марок БрО8Н4Ц2 (Cu 8% Sn 4% Ni 2% Zn) и БрО5Ц5С5 (Cu 5% Sn 5% Zn 5% Pb).